1976
DOI: 10.1017/s0022029900016046
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipolytic Gram-negative psychrotrophs in stored milk on the development of rancidity in Cheddar cheese

Abstract: SummaryThe highest incidence of lipolytic activity among the psychrotrophic Gram-negative flora of commercial raw milks was found in strains ofPseudomonas fluorescensandPs. fragi.The lipases of all of the lipolytic strains remained wholly or partly active after heat treatment at 63°C for 30 min. Two of the strains tested further had lipases which retained 20–25% of their activity even when heated at 100 °C for 10 min. Cheeses made from milks in which strains or a single strain of lipolytic Gram-negative rods (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
3
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 16 publications
4
56
3
4
Order By: Relevance
“…L'emmental français «grand-cru», dont l'odeur rance est la plus faible, est aussi le moins lipolysé. Le stockage des laits, dans le fromage de Cheddar, expliquerait, d'après Law et al (1976), l'apparition de flaveurs rances et de goûts de savon. L'origine de ces modifications étant dans ce cas due aux lipases de la flore psychrotrophe.…”
Section: Discussion Et Conclusionunclassified
“…L'emmental français «grand-cru», dont l'odeur rance est la plus faible, est aussi le moins lipolysé. Le stockage des laits, dans le fromage de Cheddar, expliquerait, d'après Law et al (1976), l'apparition de flaveurs rances et de goûts de savon. L'origine de ces modifications étant dans ce cas due aux lipases de la flore psychrotrophe.…”
Section: Discussion Et Conclusionunclassified
“…Similarly, Greek Teleme cheeses made with raw milk stored for 5 days were unacceptable for body and texture and were rejected because of rancidity, unclean flavour and bitterness due to the presence of psychrotrophic bacteria (Kalogridou-Vassiliadou and Alichanidis, 1984). Other workers (Chapman et al, 1976;Law et al, 1976;Hicks et al, 1986) have found similar off-flavours in Cheddar cheese made from cold-stored milk.…”
Section: Psychrotrophic Bacteriamentioning
confidence: 96%
“…Low pH limits the rate of lipase activity, but in some cheeses, e.g., Brie and Camembert, the pH rises to near neutrality as ripening progresses, making them especially susceptible to lipolysis (Dumont, Delespaul, Miquot, & Adda, 1977). For Cheddar cheese, however, a high concentration of lipase is needed to create the desired flavor (Law, Sharpe, & Chapman, 1976). Products such as whole milk powder may be affected by residual heat-resistant bacterial lipases.…”
Section: Enzymatic Degradationmentioning
confidence: 99%